Opera, Sound Recording, and Critical Race Theory: Making a Sub-Field Audible - Timmermans, Matthew (Current Musicology, 2021)
This review essay considers the relationships among opera, sound recording, and critical race theory, and explores them at a moment when these fields are beginning to converge. One of my concerns will be the recent and ground-breaking studies and collections on opera and race by Naomi Adele André (2017, 2019), Kira Thurman (2012, 2019), Pamela Karantonis and Dylan Robinson (2011), and Mary I. Ingraham, Joseph K. So and Roy Moodley (2016). Another will be the neglected history of opera and sound recording; notable scholars here include Karen Henson (2020), Robert Cannon (2014), and Richard Leppert (2015). Finally, I will focus on the thought-provoking analyses of race and sound by Alexander Weheliye (2005), Brian Ward (2003), Jennifer Lynn Stoever (2016) and Nina Sun Eidsheim (2019). There are obvious connections among these three bodies of scholarship, yet these connections have not yet been clearly identified and explored. Although many scholars have come to embrace opera as a material and embodied phenomenon, the artform’s dissemination, analysis, and enjoyment through sound recording is still overlooked as a site of enquiry, especially its potential as a fertile site of inquiry about identity. To overlook the issue of identity in relation to recording is to perpetuate the belief that recordings are primarily documents of performance practice. It ignores the army of technicians who invisibly craft the acoustic object, many of whom are historically white and male. This review essay seeks to address this neglect and to suggest some ways in which the processes of making and consuming opera recordings is intimately related to whiteness and anti-Blackness—but also to Black possibility. In what follows, I cast a broad net, ranging widely and at times unexpectedly. I begin with some recent events in American musicology and in the New York operatic scene; then, turn to a consideration of some of the scholarship just mentioned; and finally conclude with a brief discussion of a specific recording, the Metropolitan Opera’s “live” sound recording of the 2019 production of Gershwin’s Porgy and Bess.